2005
DOI: 10.1038/sj.gene.6364174
|View full text |Cite
|
Sign up to set email alerts
|

Functional variants in SUMO4, TAB2, and NFκB and the risk of type 1 diabetes

Abstract: Several functional genetic variants that can potentially modulate the activity of NFkB have been recently described. As reduced NFkB activity has been implicated in risk for autoimmune diabetes in the NOD mouse, these variants were tested for allelic association with type 1 diabetes (T1D) in a family based study. Alleles at markers in the TAB2/SUMO4 locus on chromosome 6q had been previously reported to be associated with T1D in two separate studies, but these studies disagreed on the identity of the risk alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Two candidate genes, SUMO4 and MAP3K7IP2, are located in the interval, and both products are suggested to be involved in alteration of NF-B activity (7,10,11). In terms of disease pathogenesis, accumulating lines of evidence indicate involvement of the NF-B pathway in the development of type 1 diabetes in humans (15) and mice (25)(26)(27)(28), further supporting the hypothesis that the SUMO4/MAP3K7IP2 locus is responsible for susceptibility to type 1 diabetes.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Two candidate genes, SUMO4 and MAP3K7IP2, are located in the interval, and both products are suggested to be involved in alteration of NF-B activity (7,10,11). In terms of disease pathogenesis, accumulating lines of evidence indicate involvement of the NF-B pathway in the development of type 1 diabetes in humans (15) and mice (25)(26)(27)(28), further supporting the hypothesis that the SUMO4/MAP3K7IP2 locus is responsible for susceptibility to type 1 diabetes.…”
Section: Discussionmentioning
confidence: 73%
“…To test whether the M55V variant of the SUMO4 gene has a population-wide effect in its association with type 1 diabetes, we performed a meta-analysis of published studies including the present study. From seven articles detected by PubMed search, six sets of data (7,9,(12)(13)(14)(15)21), including the present results, were available. Two sets of data (9,15) were excluded from the meta-analysis because some of the subjects from the Human Biological Data Interchange and the Warren Repository overlapped with those in another large-scale association study (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] However, one study reported an epistatic interaction between NFKB1 and Fc receptor-like 3 (FCRL3) gene in Spanish-Caucasian patients with rheumatoid arthritis. 19 Interestingly, FCRL3 has been recently associated with susceptibility to GD.…”
Section: Nfkb1 Promoter Polymorphism In Graves' Disease a Kurylowicz mentioning
confidence: 99%
“…There is a growing amount of evidence that variations within the NFKB1 and NFKBIA genes potentially influence the function of NFKB during development of common inflammatory and autoimmune diseases both in health and various disease conditions such as ulcerative colitis [8,53], Crohn's disease [54], RA, SLE [55], psoriatic arthritis [56], giant cell arteritis [57], Celiac disease [58], Type 1 diabetes [59], oral submucous fibrosis [60], and oral squamous cell carcinoma [60].…”
Section: The Role Of Nfkb1 and Parp-1 Inflammatory Diseasementioning
confidence: 99%